Impact of geographic distribution of accredited breast centers. Issue 11 (13th October 2020) - Pardo, Jaime A.; Fan, Betty; Valero, Monica; Alapati, Amulya; Emhoff, Isha; Mele, Alessandra; Serres, Stephanie; Davis, Roger B.; James, Ted A.
Abstract: The National Accreditation Program for Breast Centers (NAPBCs) is dedicated to improving the quality of care in patients with breast disease. Geographic distribution of health care resources is an important measure of quality, yet little is known regarding breast center allocation patterns concerning population demand and impact on health outcomes. The purpose of this study was to analyze the distribution of NAPBC programs in the United States (USA) and evaluate the impact on breast cancer survival. Using the Centers for Disease Control and Prevention 2014 data base, we identified the incidence and mortality rates for breast cancer by state. We also determined the concentration of NAPBC programs in each state (ie, the number of centers per 1000 cases of breast cancer). Data were analyzed using Spearman's (nonparametric) rank correlation coefficients. Five hundred and seventy NAPBC programs were identified. Across the United States, there was a mean of 2.8 programs/1000 breast cancer diagnoses. A positive correlation ( r = .45) between breast cancer incidence and the number of programs was identified ( P = .0009). There was no statistically significant correlation between mortality and NAPBC program concentration ( r = −0.20, P = .16). NAPBC‐accredited program distribution within the United States correlates with breast cancer incidence per state. However, the number of NAPBC programs per state did not alter overall mortality rates. Added measures beyond survival, as well as further insight into referral patterns to NAPBC programs, may be required to demonstrate the value and impact of NAPBC accreditation. Abstract : Geographical impact of National Accreditation Program for Breast Centers.